Effects of stretching in a pilates program on musculoskeletal fitness: a randomized clinical trial - Alex Lopes dos Reis; Laís Campos de Oliveira; Raphael Gonçalves de Oliveira (BMC Sports Science, Medicine and Rehabilitation, 2024)
Abstract Background The scientific literature questions the impact of stretching exercises performed immediately before muscle strengthening exercises on different components of musculoskeletal physical fitness. Pilates is a physical exercise modality that typically uses stretching exercises preceding muscle-strengthening exercises. However, no studies have investigated the effects of stretching in a Pilates program on components of musculoskeletal fitness. The aim of the present study was to verify the effects of stretching in a Pilates exercise program on flexibility, strength, vertical jump height and muscular endurance. Methods Thirty-two sedentary young women were randomized into two groups: traditional Pilates (TP), who performed flexibility and muscle strengthening exercises (n = 16), and nontraditional Pilates (NTP), who only performed muscle-strengthening exercises (n = 16). Sessions took place 3 times a week for 8 weeks. The following tests were performed pre- and postintervention: 10-RM knee extensors, vertical jump, handgrip, 1-min sit-ups, Sorensen and sit-and-reach. The occurrence of adverse events was recorded throughout the intervention and compared between groups using odds ratio (OR). To compare the results of motor tests between groups, ANCOVA or Mann‒Whitney U test was used for parametric and nonparametric data, respectively. The data were analyzed by intention-to-treat. Results After intervention, the TP was superior to NTP for the sit-and-reach test, with a large effect size (d = 0.87; p = 0.035), with no differences between groups for the other tests. Intragroup comparisons showed significant differences (p < 0.05) for TP and NTP for improvement in 10-RM knee extensors and vertical jump measurements, while only TP showed significant intragroup improvement (p < 0.05) for the sit-and-reach test. A greater chance of experiencing pain or other discomfort as a result of exercise was shown by NTP (OR = 4.20, CI95% 0.69 to 25.26). Conclusion Our findings demonstrated that stretching exercises performed at the beginning of sessions in a Pilates program did not impair or enhance the development of strength, vertical jump height and muscular endurance in young women. However, only the Pilates program with stretching improved flexibility and reduced the chances of adverse events such as musculoskeletal pain and other discomfort resulting from the exercise protocol. ClinicalTrials.gov NCT05538520, prospectively registered on September 16, 2022.